Cerebral venous sinus thrombosis: risk factors and outcomes. (4th April 2011) - Ismail, N; Clarke, R; John, C M
Abstract : Introduction: Cerebral venous sinus thrombosis (CVST) is relatively rare and notoriously difficult to diagnose. It can be life-threatening and is known to cause long term neurological deficit. Aim: Determine the underlying predisposing factors and outcome of children with CVST. Methods: Retrospective analysis of case notes of patients diagnosed with CVST between 1997 and 2009 in a tertiary Children's hospital. Results: Over this 12 year period, 17 patients were identified from clinical coding (10 male, 7 female). Median age of presentation was 5.5 years (range 2 days–17 years). 6/17 had vomiting as a presenting feature. With regards to risk factors, 6/17 patients had infection of the ears/mastoid as the main predisposing factor, 3/17 had leukaemia and 2/17 had central lines in situ. 2/17 developed CVST secondary to non accidental head injury. One 14 year old girl was on the contraceptive pill. One patient had Transposition of great vessels. Only one patient was clinically significantly dehydrated. There was no family history of thrombophilia in any patient. With regards to clinical signs, 11/17 had abnormal neurological signs. 6/17 had papilloedema. Only one patient was hypertensive. With regards to investigations, all patients had MR venography (MRV) done. 3/17 had positive bacterial cultures (2 blood, 1 pus). Thrombophilia screens were abnormal in 5/17 (2 heterozygote for factor V wild type). With regard to outcome, 9/17 had complete recovery. 2/17 had residual neurological deficit, 2/17 suffered persistent headache, 2 died and no follow-up data was available on 2 patients. Conclusion: The commonest predisposing factors for CVST are sinus/mastoid infections. MRI/MRV remains the gold standard for diagnosis. There needs to be a high index of suspicion and a low threshold to perform MRI scans in suspected CVST as it can be life-threatening and can cause long term neurological deficit.